Land Suitability and Potential Agriculture Analysis to Regional Development Based on Agro-Tourism - Muhammad Anshar; Irsyadi Siradjuddin; Muhammad Rezki; Amirin kusmiran (Universitas Diponegoro, Indonesia, 2022)
Bontolempangan District is one of the districts included in the spatial planning area of the Gowa Regency. The development of tourism potential and agricultural land resources is a major part of the Gowa Regency spatial plan (RTRW 2012-2032). Therefore, this research investigates the potential of agricultural commodities and the carrying capacity of their land so that they can be used as a reference to become an agricultural-based tourism area. The agricultural potential was analyzed using the location quotient (LQ) and dynamic location quotient (DLQ) methods, while the carrying capacity of agricultural land was analyzed using land suitability analysis. From the LQ and DLQ analysis, robusta coffee, cocoa, cashew, candlenut, and arabica coffee are the leading agricultural commodities. Based on the land suitability analysis, the carrying capacity of the land for superior agricultural commodities is categorized into themoderate suitable level (S2) with an area of 2968.22 ha for Robusta coffee, 1202.30 ha of cocholate, 2227.22 ha of cashew nuts, 2253.47 ha of candlenut, 3235.91 ha of Arabica coffee ha, and sweet potatoes covering an area of 952.78 ha. Thus, leading agricultural commodities can be developed into agricultural-based tourism areas or agro-tourism.